Pengaruh Brand Awareness, Brand Association, dan Percieved Quality - Wasil, Mohammad (Faculty of Economics and Business Mulawarman University, 2017)
After a literature review and hypothesis formulation, data collected through questionnaire method to 82 people consumer of water purifiers Forbes in Samarinda which is obtained by using the purposive sampling technique. Thisresearch was conducted by using multiple linier regression. The conducted and analysis of data obtained with quantitative data. Quantitative data analysis are includes of : multiple regression analysis, hypothesis testing with the t test and F test, also the analysis of the correlation coefficient (R), and coefficient of determination (R ).Based on the results of the observation, obtained the following regression equation : Y= 0,834 + 0,106X1 + 0,490X2 + 0,244X3Where the purchase decision variable (Y), brand awareness (X1), brand association (X2), and the perceived quality (X3). testing the hypothesis using the t test showed that the three independent variables brand awareness, brand associations, and perceived quality, positive influence on purchasing decisions. Coefficient of regression equal to (R) 0621a is translated into a table that all the variables of brand awareness, brand associations, and perceived quality, has a very strong influence on the consumer's decision to purchase a water filter Forbes. Asses R2 equal to 0,386 it means 38,6% variable purchase decision (Y) is influenced by three independent variables (X) and the remaining 61.4% is explained by other variables not included in this study. Keyword : purchasing decision, brand awareness, brand associations, andb perceived quality